SERVICE INNOVATION MANAGEMENT PRACTICES AND PRICING PRACTICES FOR PERFORMANCE IN MALAYSIAN TELECOM - Seyedeh Khadijeh Taghizadeh,; K. Jayaraman,; Syed Abidur Rahman,; Ali Quazi, (Asian Academy of Management Journal, 2017)
This study aims to test the role of pricing practices as an intervening variable in the relationship between service innovation management practices (innovation strategy, innovation process, cross-functional organisation, tools/technology, and system integration) and firms’ performance in an emerging economy. Data were collected from 249 managers representing the Malaysian telecommunications sector using a structured questionnaire. Structural equation modelling (SEM) with SmartPLS software, version 3, was used to achieve the research objectives and to analyse the measurements and structural model. The results showed that, whereas innovation strategy, innovation process, cross-functional organisation, and system integration positively influence pricing practice, tools and technology has an insignificant effect on pricing practice. Interestingly, pricing practice mediates the relationship between innovation strategy and system integration regarding firm performance. The findings of this study suggest that, in the formulation of such a strategy, service firms should consider the pricing factor. Telecommunications service providers could use this model to implement pricing practices particularly driven by innovation practices to achieve the desired performance. The study could also assist managers in understanding suitable pricing practices in the context of the telecommunications industry. The originality of this study lies in the effort to adjoin service innovation management practices with pricing practices that lead to improving the performance of the telecommunications industry.